Enforcement of Criminal Penalties for Drug Abuse Committed by Police Officers - Fajar, Alim; Iftiati, Indah; Soviana, Silvania (JUSTISI, 2024)
Policing is a government function responsible for maintaining public order and safety. As an institution, the police have the authority to enforce laws and provide guidance and services to the community. This study investigates the enforcement of criminal penalties for drug abuse committed by police officers. The research adopts a normative legal approach, anchoring itself in the legal framework outlined within Law Number 35 of 2009, specifically focusing on the realm of Narcotics. This research method employs a normative juridical approach, wherein the issues arising in the field are examined through legal materials discussing the abuse of narcotics. The study finds that judges impose criminal sanctions on police officers who abuse narcotics in the same way as civilians, as specified in Law Number 2 of 2002 concerning the Indonesian National Police Article 29 paragraph (1). This underscores the civilian status of police officers, making it clear that they fall outside the purview of military law.